An analysis of news containing cyberbullying in the metaverse - Yildiz, I?lkay; Tanyildizi, Nural I?mik (IGI Global, 2022)
The rapid progress of technological developments and their opening to the use of societies has brought with it various problems. Although the internet makes our lives easier, bullying has started to be seen in this area. The subject of cyberbullying, which should be addressed in a wide area from economy to politics, from social life to culture, has also manifested itself in the metaverse area. This study examines how the Turkish national press handles cyberbullying in the metaverse area. News about Metaverse has been published in many publications. The news that deals with cyberbullying and solution suggestions are only included in this study. In the Turkish national press, a total of six stories about cyberbullying in the metaverse area were reached. The news usually consists of harassment, precautionary, and solution suggestions. They were analyzed by the discourse analysis method. While performing discourse analysis, both macro and micro analyses were made. © 2023, IGI Global. All rights reserved.